Corporate Sector Resilience in India in the Wake of the COVID-19 Shock - Gornicka, Lucyna (IMF Working Papers; Working Paper, 2021)
To assess the resilience of India's corporate sector against COVID-19-related shocks, we conducted a series of stress tests using firm-level corporate balance sheet data. The results reveal a differential impact across sectors, with the most severe impact on contact-intensive services, construction, and manufacturing sectors, and micro, small, and medium enterprises. On policy impact, the results highlight that temporary policy measures have been particularly effective in supporting firm liquidity, but the impact on solvency is less pronounced. On financial sector balance sheets, we found that public sector banks are more vulnerable to stress in the corporate sector, partly due to their weaker starting capital positions. When considering forward-looking multiperiod growth scenarios, we find that the overall corporate performance will depend on the speed of recovery. A slower pace of recovery could lead to persistently high levels of debt at risk, especially in some services and industrial sectors.